مقارنة تأثير الفحم الحيوي و تأقير الملوحة على التربة المزروعة بنبات الفول - بيكي ريان; فقيري حنان (جامعة الوادي university of eloued, 2025)
This study aimed to compare the effects of both salt stress and soil amendment with biochar on a range of physiological and morphological traits of faba bean (variety Aguadulce) during the vegetative stage. The experiment was conducted under controlled conditions using four treatments: untreated soil (SV), soil saline with two levels of sodium chloride (70 mmol/L SVN1 and 150 mmol/L SVN2), and soil amended with biochar (SVB(. The measurements studied included germination percentage, germination rate, stem length, leaf area, chlorophyll (A and B) concentrations, and plant dry weight. The results showed that high salinity (150 mmol/L) had a clear negative effect on all traits, with the lowest values recorded, indicating the inhibitory effect of extreme salinity due to osmotic stress and ionic toxicity. Moderate salinity (70 mmol/L) showed a mixed effect, with a slight stimulation of germination speed and chlorophyll concentration compared to the control, indicating an adaptive response at lower salinity levels. Biochar, on the other hand, improved germination speed and leaf area of faba beans by improving soil properties, but it did not significantly affect chlorophyll, possibly due to its properties or its interaction with salinity.
فيزيولوجيا النبات
Keywords: faba Bean (Vicia faba L.); Salinity; Biochar; Soil; Germination; الفحم